2021
DOI: 10.47577/tssj.v26i1.4936
|View full text |Cite
|
Sign up to set email alerts
|

What Justice? Whose justice?: Rethinking climate justice through climate change impacts and options for adaptation in Africa

Abstract: Climate change is considered a justice issue based on the causes of the phenomenon, its impacts and polices designed to manage it. Previous studies have revealed that Africa and the entire developing world contribute less to Green House Gas emissions (GHG) which is the leading cause of climate change, but they suffer the most from its consequences, whereas the first world, whose contribution to GHG is immense but the impact of the phenomenon to them is minimal. In this article, I made use of climate change imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This dimension emphasises ethical responsibilities to future generations, advocating for policies that mitigate climate change and its impacts on the yet unborn. Intergenerational justice claims that current climate-related policies often do not adequately address the intergenerational impacts of climate change Hughes and Hoffmann (2020), Mugambiwa (2021), Rahman (2022. It calls for robust legal frameworks that safeguard the rights and interests of future generations.…”
Section: Understanding Climate Justice As a Multidimensional Approach...mentioning
confidence: 99%
“…This dimension emphasises ethical responsibilities to future generations, advocating for policies that mitigate climate change and its impacts on the yet unborn. Intergenerational justice claims that current climate-related policies often do not adequately address the intergenerational impacts of climate change Hughes and Hoffmann (2020), Mugambiwa (2021), Rahman (2022. It calls for robust legal frameworks that safeguard the rights and interests of future generations.…”
Section: Understanding Climate Justice As a Multidimensional Approach...mentioning
confidence: 99%
“…According to recent studies also confirmed that anthropogenic influences on global warming are becoming more important. Greenhouse gases in the lower atmosphere of Earth are one of the main causes of global climate change (Mugambiwa.,2021). ; Supriyanto.,2017).…”
Section: Sources Of Cognitive Informationmentioning
confidence: 99%
“…However, international agreements led by state actors have not comprehensively provided solutions to the imbalance in global climate justice [2]. Despite bearing the brunt of climate risks, rural communities are often excluded from climate policy discussions due to unequal access to information, perpetuating existing inequalities [3]. Until now, the issue of climate change continues to evolve and remains a concern almost thirty years later.…”
mentioning
confidence: 99%